Electrothermal Failure Physics of GaN Schottky Diodes Under High-Temperature Forward Biasing - Nahid Sultan Al-Mamun; Yuxin Du; Jianan Song; Rongming Chu; Aman Haque (Micromachines)
The reliability of GaN-based devices operating under high temperatures is crucial for their application in extreme environments. To identify the fundamental mechanisms behind high-temperature degradation, we investigated GaN-on-sapphire Schottky barrier diodes (SBDs) under simultaneous heating and electrical biasing. We observed the degradation mechanisms in situ inside a transmission electron microscope (TEM) using a custom-fabricated chip for simultaneous thermal and electrical control. The pristine device exhibited a high density of extended defects, primarily due to lattice mismatch and thermal expansion differences between the GaN and sapphire. TEM and STEM imaging, coupled with energy-dispersive X-ray spectroscopy (EDS), revealed the progressive degradation of the diode with increasing bias and temperature. At higher bias levels (4–5 V) and elevated temperatures (300–455 °C), the interdiffusion and alloying of the Au/Pd Schottky metal stack with GaN, along with defect generation near the interface, resulted in Schottky contact failure and catastrophic device degradation. A geometric phase analysis further identified strain localization and lattice distortions induced by thermal and electrical stresses, which facilitated diffusion pathways for rapid metal atom migration. These findings highlight that defect-mediated electrothermal degradation and interfacial chemical reactions are critical elements in the high-temperature failure physics of GaN Schottky diodes.